Long-Term Traumatic and Asymptomatic Aorto-Right Atrial Fistula - Lima,Sandro Gonçalves de (2019)
Abstract Aorto-atrial fistulas due to cardiac trauma are rare, and survivors require immediate surgical correction. Here, we report a case of an aorto-right atrial fistula due to penetrating trauma after a 16-year evolution, which developed symptoms of acute coronary syndrome and was treated with myocardial revascularization and correction of the aorto-cameral fistula.